APE2 Is a General Regulator of the ATR-Chk1 DNA Damage Response Pathway to Maintain Genome Integrity in Pancreatic Cancer Cells - Hossain, Md Akram; Lin, Yunfeng; Driscoll, Garrett; Li, Jia; McMahon, Anne; Matos, Joshua; Zhao, Haichao; Tsuchimoto, Daisuke; Nakabeppu, Yusaku; Zhao, Jianjun; Yan, Shan (Frontiers in Cell and Developmental Biology, 2021)
The maintenance of genome integrity and fidelity is vital for the proper function and survival of all organisms. Recent studies have revealed that APE2 is required to activate an ATR-Chk1 DNA damage response (DDR) pathway in response to oxidative stress and a defined DNA single-strand break (SSB) in Xenopus laevis egg extracts. However, it remains unclear whether APE2 is a general regulator of the DDR pathway in mammalian cells. Here, we provide evidence using human pancreatic cancer cells that APE2 is essential for ATR DDR pathway activation in response to different stressful conditions including oxidative stress, DNA replication stress, and DNA double-strand breaks. Fluorescence microscopy analysis shows that APE2-knockdown (KD) leads to enhanced γH2AX foci and increased micronuclei formation. In addition, we identified a small molecule compound Celastrol as an APE2 inhibitor that specifically compromises the binding of APE2 but not RPA to ssDNA and 3′-5′ exonuclease activity of APE2 but not APE1. The impairment of ATR-Chk1 DDR pathway by Celastrol in Xenopus egg extracts and human pancreatic cancer cells highlights the physiological significance of Celastrol in the regulation of APE2 functionalities in genome integrity. Notably, cell viability assays demonstrate that APE2-KD or Celastrol sensitizes pancreatic cancer cells to chemotherapy drugs. Overall, we propose APE2 as a general regulator for the DDR pathway in genome integrity maintenance.